Pengaruh Kehadiran (Absensi) terhadap Nilai Hasil Ujian di Politeknik Citra Widya Edukasi – Bekasi - . Basuki (JURNAL CITRA WIDYA EDUKASI, 2020)
The purpose of this research is to determine the level of significance of the influence of the presence of students in attending lectures on the test result. The research method used is descriptive quantitative by calculating the correlation between the two variables. Whereas data processing is quantitative by using statistical analysis. The sample used was the Standard Operating Procedure Logistics course, which was attended by 117 students in Logistics Management Department class of 2017 and 2018. The result showed that the presence of students in attending lectures (absenteeism) had a strong influence on test score (positive correlation). While the value of exam result is influenced by attendance by 33.28% and 66.72% is influenced by other factors.